ETIKA BERMEDIA SOSIAL MENJAMIN KEUTUHAN PERKAWINAN KATOLIK DI PAROKI SANTO PAULUS BUNTOK - Refani Refani; Fransiskus Janu Hamu; Timotius Tote Jelahu (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2019)
This study aims to detetermine how important social media ethics in the life of the catholic family, as a maens to help outgoing Catholic family maintain the integraty of marriage in the Parish of Saint Paul Buntok. Through this study, it is hoped that Catholic families use social media well and wisely in the family life, and make social media as communication and catechetical suggestion in this modern era in order to cultivate the faith of others. The method used in this study is a qualitative method with a phenomenological approach. As for the research steps used are : conversations with informants, informant profiles, datermination of themes, reflection, implications, synthesis, prospects or possibilities that will occur. The results obtained through research conducted by the author found that families in the parish of Saint Paul Buntok did not all know ethics in using social media. Through this reseach, the author also see that families in the parish of Saint Paul Buntok use social media in building good relations and communication